Pengukuran Metrik Kompleksitas Model Proses Bisnis Pondok Pesantren - Muhammad Ainul Yaqin; Dian Permana Putra; Faizal Armas Fata; Lailatul Maghfiroh (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Yudharta Pasuruan)
Today's world business organizations make use of digital information systems to provide an understanding of the management of business processes that they run, including boarding schools. To find out the quality of the boarding school business process, a modeling of the business process is carried out which will be used as a project to measure a business process in the boarding school. Therefore, the calculation process is carried out through metric indices in the boarding school business process model. This is a basic c onsideration that is used as a reference for calculating the metrics that can be obtained from modeling existing business processes. In this paper, a calculation of the business process model of the boarding school is carried out through BPMN diagram types.